The Millenial Consideration in Intention to Use E-Wallet in The Covid-19 Pandemic - Humairoh Humairoh; Mohammad Annas (Dinasti Publisher, 2023)
The government's effort to prevent the spread of Covid-19 is to avoid physical distancing so that millennials making payment transactions use more digital transactions. Digital wallets have been seen as a facility that provides ease of use and usefulness in transactions. However, there are still many millennials who don't know and don't feel comfortable using e-wallets, especially when it comes to payments. This study aims to analyze the brand image, perceived ease of use, and perceived usefulness for the intention to use digital wallets (e-wallets) through millennial considerations as an intervening variable during the Covid-19 pandemic in SMEs in Tangerang City. The research sample was 96 respondents using purposive sampling techniques, namely millennials who use e-wallets in making payments. The instrument used was a questionnaire with a Likert scale of 1-5. This study uses path analysis techniques with the Smart PLS program. The results of this study indicate that during the Covid-19 pandemic, millennials in the intention to use e-wallets was influenced by brand image, perceived ease of use, and perceived usefulness through millennial considerations as an intervening variable with an R2 value of 0.675. The results of this study have implications for SMEs business actors to provide an e-wallet payment system.